The integration of technological, didactic and disciplinary skills in the initial training of support teachers - Alessandra La Marca; Valeria Di Martino (Formare, 2021)
This paper analyses training support teachers’ knowledge as described by the Technological Pedagogical Content Knowledge framework (TPCK) (Mishra & Koehler, 2006) based on Shulman’s PCK (1986). Technological resources offer indisputable opportunities to teachers who want to renew the contents and strategies of their teaching and provide students with active learning processes; yet they offer some reflections about the methodologies used in support teacher training considering, among the other factors, the variety of qualifications that allow access to the training course. The results obtained with a sample of 1591 teachers enrolled in the support teacher specialization course, run by the University of Palermo, as well as the reflections related the TPACK, could allow to adapt the ICT courses to the real initial skills of the students, contributing to the training of support teachers able to use digital resources in an inclusive and effective way.